IMPACTS OF LOW RANK COAL UTILIZATION IN THE COAL FIRED POWER PLANT THAT WAS DESIGNED TO USE SUB - BITUMINOUS COAL - cahyadi, cahyadi; Yurismono, Hari (185P -3466)
Most of the existing coal fired power plants in Indonesia that have capacity of 400-600MW is designed using sub-bitumonous coal intake. This coal has a caloric value of 5,000 kcal/kg (a.r.). Considering the coal price of sub-bituminous tends to raise, some power plant have switched to use a low rank coal having a caloric value of 4,200 kcal/kg (a.r.). Indonesian Coal Index (ICI), in November, 2008 indicated that the coal having caloric value of 5,800; 5,000 and 4,200 kcal/kg (a.r.) are US$ 93, 68 and 41 per ton (FOB) respectively.  Low rank coal utilization in the existing coal fired power plant that was designed for the  sub-bituminous coal intake are reviewed both in technical and economic aspect and its impacts on the power plant performance.